Intussusception in Kumasi - Ghana: Analysis of 84 Cases (Journal of Science and Technology, 2016)
La retrospective study, eighty-four patients treated for intussusception at the Komofo Anokye Teaching Hospital in Kumasi-Ghana within a period of ten years were analysed and discussed with respect to age and sex distribution, preoperative differential diagnosis, anatomical typing, intraoperative findings. postoperative morbidity and mortality, as well as complications after surgery.Approximately 8.4 cases of intussusception were recorded in the hospital each year, with an overall mortality rate of 9.5%. Fifty-nine (70.2%) patients were males and twenty-five (29.8%) were females. The majority (85.7%) were children; the rest (14,3%) were adults. In forty-four cases, the intussusception was associated with a mobile caecum. Other intraoperative findings included enlarged mesenteric lymph nodes, adhesions, malrotation, lymphoma of the bowel, large bowel polyp and a blind loop of a side-to-side intestinal anastomosis. These and also the possible association of intussusception with herbal enemas are considered in this study as moments favouring the occurrence of intussusception.